Prevalence of comorbidities in women with and without breast cancer in Soweto, South Africa: Results from the SABC study - Ayeni, O A (S Afr Med J, 2019)
BACKGROUND. Comorbidities occurring concurrently in breast cancer patients can be burdensome, as they may negatively influence time and stage of presentation. OBJECTIVES. To describe the comorbid health conditions among South African (SA) black women with and without breast cancer and to determine factors associated with advanced-stage presentation of breast cancer. METHODS. A population-based case-control study on breast cancer was conducted in black women in Soweto, SA, the SABC (South Africa Breast Cancer) study. Lifestyle information and blood samples were collected from 399 women with histologically confirmed new cases of invasive primary breast cancer, recruited prior to any therapy, and 399 age- and neighbourhood-matched controls without breast cancer. We compared self-reported metabolic diseases, depression, anthropometric measurements, blood pressure, HIV status and point-of-care lipid and glucose levels between patients with breast cancer and the control group. RESULTS. In the whole population, the mean (standard deviation) age was 54.6 (12.9) years, the majority (81.2%) of the participants were overweight or obese, 85.3% had abdominal adiposity, 61.3% were hypertensive, 47.1% had impaired fasting plasma glucose, 8.4% had elevated total cholesterol, 74.8% had low high-density lipoprotein and 10.9% were assessed to be depressed. Ninety-one percent of the whole cohort had at least one metabolic disease. In the breast cancer group, 72.2% had one or more metabolic diseases only (HIV-negative and no evidence of depression), compared with 64.7% of the control group. From a multivariate logistic regression adjusted model, higher household socioeconomic status conferred a 19% reduction in the odds of having advanced-stage breast cancer at diagnosis, while hypertension, dyslipidaemia and HIV were not significantly associated with stage at breast cancer diagnosis in the adjusted model. CONCLUSIONS. A large proportion of women experience several comorbidities, highlighting the need to address the chronic noncommunicable disease epidemic in SA and to co-ordinate multidisciplinary primary-, secondary- and tertiary-level care in the country’s complex healthcare system for better outcome.